The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0153415
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality, Rather than Nutrient Addition or Vegetation Types, Influenced Short-Term Temperature Sensitivity of Soil Organic Carbon Decomposition

Abstract: The response of microbial respiration from soil organic carbon (SOC) decomposition to environmental changes plays a key role in predicting future trends of atmospheric CO2 concentration. However, it remains uncertain whether there is a universal trend in the response of microbial respiration to increased temperature and nutrient addition among different vegetation types. In this study, soils were sampled in spring, summer, autumn and winter from five dominant vegetation types, including pine, larch and birch f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
0
5
1
Order By: Relevance
“…Tian et al (2016) demonstrated that N addition does not influence soil microbial CO 2 emission from a topsoil in a laboratory incubation. Several field studies also reported lower soil microbial CO 2 emissions with N addition compared to controls due to changes in microbial composition (Bowden, Davidson, Savage, Arabia, & Steudler, 2004;Mo et al, 2008;Phillips & Fahey, 2007;Qian et al, 2016;, but here no changes were observed. The response of CO 2 emission to N addition might also be related to soil C substrate availability.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Tian et al (2016) demonstrated that N addition does not influence soil microbial CO 2 emission from a topsoil in a laboratory incubation. Several field studies also reported lower soil microbial CO 2 emissions with N addition compared to controls due to changes in microbial composition (Bowden, Davidson, Savage, Arabia, & Steudler, 2004;Mo et al, 2008;Phillips & Fahey, 2007;Qian et al, 2016;, but here no changes were observed. The response of CO 2 emission to N addition might also be related to soil C substrate availability.…”
Section: Discussioncontrasting
confidence: 50%
“…Our result is supported by some previous studies. For example, Mori et al (2016) found that CO 2 emission rates in tropical forest soils were stimulated by P addition at high C concentrations (1 mg C/g soil was added as glucose) but not at low C conditions (0.1 mg g −1 soil), whereas Qian et al (2016) reported that there was no response of soil microbial CO 2 emission to P addition. Indeed, in this study, the EV-RT soil in Puerto Rico with the highest C content (7.21%) showed the strongest response to P addition among the four soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the two to four month lag length of NDVI in response to temperature for distinct sub-watersheds reveals that the vegetation may not have a synchronous response to temperature changes. As vegetation mainly accumulates nutrients and organic matter in spring and grows in summer and autumn [29], the distinct dominant and diversity of the vegetation types would be the main cause of different legacy effect for NDVI in response of the temperature. The agricultural area (upstream) presented a faster responce to temperature than the forest conservation area in the midstream and forest-urban mixed area in the downstream, which may be due to the short growth cycle and rapid growth rate of the crops [30].…”
Section: Ndvi Response To Temperaturementioning
confidence: 99%